Anti-Breast Cancer Effect of 2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione in vivo and in vitro Through MAPK Signaling Pathway - Zhou X; Wu X; Qin L; Lu S; Zhang H; Wei J; Chen L; Jiang L; Wu Y; Chen C; Huang R (Dove Medical Press, 2020)
Xing Zhou,* Xingchun Wu,* Luhui Qin, Shunyu Lu, Hongliang Zhang, Jinbin Wei, Lixiu Chen, Luhui Jiang, Yani Wu, Chunxia Chen, Renbin Huang Pharmaceutical College, Guangxi Medical University, Nanning 530021, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Renbin Huang; Chunxia Chen Tel +86 771 5339805Fax +86 771 5358272Email huangrenbin518@163.com; Chunxia251401@126.comBackground: 2-Dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD) has been reported to inhibit a variety of cancer cell lines. The purpose of this study was to investigate the effects of DMDD on 4T1 breast cancer cells and the effects of DMDD on 4T1 breast cancer in mice and its molecular mechanisms.Methods: 4T1 breast cancer cells were treated with different concentrations of DMDD, and their proliferation, apoptosis, cell-cycle distribution, migration, and invasion were detected by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT, Acridine orange and ethidium bromide dual staining analysis (AO/EB) dual staining, flow cytometry, scratch test, and the Transwell assay. Relative quantitative real-time qPCR analysis and Western blot were applied to examine the expression levels of related genes and proteins. In animal experiments, we established a xenograft model to assess the anti-breast cancer effects of DMDD by evaluating the inhibition rate. The apoptotic activity of DMDD was evaluated by hematoxylin-eosin (HE) staining, transmission electron microscope (TEM) analysis and TdT-mediated dUTP nick end labeling (TUNEL) assays. The mRNA expression levels of MAPK pathway components were detected by relative quantitative real-time qPCR. In addition, the protein expression levels of MAPK pathway components were assessed through immunohistochemical assays and Western blotting.Results: Experiments showed that DMDD could inhibit the proliferation, migration, invasion of 4T1 cells and induce cellular apoptosis and G1 cell cycle arrest. Moreover, DMDD down-regulated the mRNA expressions of raf1, mek1, mek2, erk1, erk2, bcl2, and up-regulated the mRNA expression of bax. DMDD reduced the protein expressions of p-raf1, p-mek, p-erk, p-p38, Bcl2, MMP2, MMP9 and increased the protein expressions of Bax and p-JNK. The results showed that DMDD can effectively reduce the tumor volume and weight of breast cancer in vivo, up-regulate the expression of IL-2, down-regulate the expression of IL-4 and IL-10, induce the apoptosis of breast cancer cells in mice, and regulate the expression of genes and proteins of the MAPK pathway.Conclusion: Our study indicates that DMDD can inhibit proliferation, migration, and invasion and induces apoptosis and cell-cycle arrest of 4T1 breast cancer cells. Also, our findings indicate that DMDD induces the apoptosis of breast cancer cells and inhibits the growth in mice. Its mechanism may be related to the MAPK pathway.Keywords: DMDD, breast cancer, MAPK signaling pathway, Bcl-2 family